Cryptanalysis of NTRU: a post quantum algorithm - Arora, Kanupriya (Nanyang Technological University, 2024)
The rapid advancement of quantum computing poses a significant threat to the security of traditional cryptographic algorithms. This study presents an in-depth analysis of the NTRU cryptosystem, a front-runner in post-quantum cryptography. NTRU, a lattice-based cryptosystem, is presented as a promising alternative due to its resistance to quantum computational attacks and efficiency in operations. This study thoroughly investigates NTRU’s key generation, encryption, and decryption processes. It aims to identify potential vulnerabilities within the NTRU algorithm by examining various sophisticated cryptanalytic attacks, including lattice reduction, multiple transmission, and meet-in-the-middle attacks.